Repetitive transcranial magnetic stimulation for post-stroke non-fluent aphasia: a systematic review and meta-analysis of randomized controlled trials - Cheng, Jing; Jiang, Yijing; Rao, Ting; Yang, Yihan; Liu, Yanping; Zhan, Ying; Yang, Shanli (Frontiers in Neurology, 2024)
Objective To systematically evaluate the efficacy and safety of repetitive transcranial magnetic stimulation (rTMS) on language function in patients with non-fluent aphasia post-stroke. Methods We selected randomized clinical trials (RCT) that involved stroke patients with non-fluent aphasia, whose intervention was rTMS vs. no therapy or other therapy. Two researchers autonomously reviewed the literature based on the specified criteria for inclusion and exclusion and completed the process of data extraction, data verification, and quality evaluation. Meta-analysis was performed using RevMan 5.41 and Stata MP 172, while the assessment of risk of bias was carried out utilizing the Risk of Bias version 2 tool (RoB2)3. Results The meta-analysis involved 47 RCTs, encompassing 2,190 patients overall. The indexes indicated that rTMS has the potential to decrease the severity of non-fluent aphasia in stroke patients, including improvement of the capability of repetition, naming, and spontaneous language. The determination of BDNF in the serum of patients was also increased. In addition, rTMS reduced the likelihood of depression in stroke patients. Conclusion To summarize the relevant studies, rTMS has significant effects on improving the language abilities of stroke patients suffering from non-fluent aphasia, including the abilities of repetition, naming, and spontaneous language.